The Factor Affecting Seam Strength Sewn With Ultrasonic Sewing Machine - แสงวัฒนะ, พิษณุ; เตชธรรมรักข์, ปลื้มจิตต์ (Frontiers in Engineering Innovation Research, 2008)
Typically, most of the garments are sewn with threads. However, this is the disadvantage in the case of skiing product, rain protecting cloth where the water resistant property is concerned. Thus, the application of ultrasonic was used in place of sewing machine. The research aims to investigate the factors affecting the seam strength welded with ultrasonic sewing machine. Three woven samples made of polyester, nylon and nylon coated with Polyurethane (PU) were used. It was found that the seam strength of Fabrice before and after 5th wash is not much different. It is apparent that the speed of welding affected the seam strength.